2017
DOI: 10.1186/s12912-017-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

A final-year nursing student survey: rural attitudes, perceived competencies and intention to work across five Asian countries

Abstract: BackgroundShortages and maldistribution of nurses remain significant problems in many countries. Having appropriate intervention strategies to retain nurses in underserved areas, where they are most needed, are crucial for health system strengthening. This study aimed to quantify attitudes to working in rural areas, perceived competencies, and intention to work among final-year nursing students, and to analyze the associations between those factors and their background characteristics across five countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Their results showed that "working in teams" gained the highest score after the dimension "effective communication with other members of the healthcare team". 16 This result may be due to the mediating role of nurses in health care system; nurses learn and experience teamwork skills from the outset. Gaupp et al added that the students' participation increased after PS education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results showed that "working in teams" gained the highest score after the dimension "effective communication with other members of the healthcare team". 16 This result may be due to the mediating role of nurses in health care system; nurses learn and experience teamwork skills from the outset. Gaupp et al added that the students' participation increased after PS education.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the present study, the lowest mean score difference was related to "managing safety" because our participants included first-year nursing students with no clinical experiences and could not manage safety competencies effectively. 16,18 As a result, students need to acquire theoretical and practical safety management skills to manage other positions. 19 VanDenKerkh of et al demonstrated that the score of "managing safety" was higher among the clinically educated nurses than the theoretically-educated nurses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies focused on other health students such as medical,10 18optometry9 and midwifery,11or including nurses but mixed in with the others 8 19–2122 and final-year students 23. Several rural health-related studies conducted in Indonesia had different subjects and aims to the current study, such as identifying the medical students’ rural preferences,18 assessing the rural health programmes and not the students’ preferences24 25 and concerning only the attracting factors 21.…”
Section: Introductionmentioning
confidence: 99%